Teaching Creative Thingking : Developing learners who generate ideas and can think critically - Lucas, Bill, 1956- (Pedagogy for a changing world)
Teaching Creative Thinking' explores the ways in which teachers can help learners to cultivate the dispositions which evidence suggests are going to be valuable to them both at school and in later life. Creative thinking is original, purposeful and val